Healing experience for family caregivers after an intensive care unit death. Issue Volume 12:Issue e4(2022) (4th February 2019) - DeSanto-Madeya, Susan; Willis, Dan; McLaughlin, Julie; Boslet, Aristotle
Abstract : Objectives: Family caregivers suffer a high burden of emotional and psychological distress following the death of a loved one in the intensive care unit and often struggle to heal in the weeks following their loss. The purpose of this hermeneutic phenomenological study was to describe and interpret the experience of healing for family caregivers six weeks following the death of a loved one in the ICU. Methods: Semi-structured telephone interviews were conducted with a purposive sample of twenty-four family caregivers six weeks following the death of their loved ones in the ICU. Qualitative analysis techniques were used to identify common themes central to the experience of healing across all interviews. Results: Seven themes were interpreted from the data: searching for clarity from a time of uncertainty; riding an emotional rollercoaster; seeking peace in one's decisions; moving forward with each new day; taking comfort in the memories; valuing layers of support; and discovering life on one's own. Conclusion: By identifying and gaining an understanding of healing following the death of a loved one in the ICU, nursing and other healthcare providers have an opportunity to promote healing and positively impact family caregiver's bereavement.